i-Swift: Newton Forward Divided Difference Interpolation-Distance and time arrival calculator for teaching and learning processes - Mohd Rohaidi, Nur Nadhirah; Panji, Elaziera; Harun, Nurzalina; Sadikin, Zubaidah; Rathi, Sidik; Mohd Sidek, Nur Zafirah; Batcha, Siti Rahimah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
i-Swift was designed to assist the public navigate and manage logistics industries. People often struggle with estimating travel distances based on the time taken, especially during exercise routines, outdoor activities, or daily commutes. The lack of a fast and accurate method to calculate distance from elapsed time hampers individuals' ability to monitor progress, plan activities, and make informed decisions about their physical movement. Nevertheless, calculating the optimum distance may be tedious and error-prone due to doing it manually. As a solution, with this graphical user interface (GUI), referred to as i-Swift, it can help to improve travel and commuting experience by estimating the distance using The Newton Forward Divided Difference Interpolation Formula. i-Swift also assists to determine the mathematical equations for providing instant, accurate distance estimates. This app takes the complexity out of distance calculations, utilizing the Newton Forward Divided Difference Interpolation Formula to swiftly determine distances based on time. i-Swift presents an innovative solution catering to both the public and the logistics sectors. By simplifying travel for the public, it eliminates hurdles, ensuring stress-free journeys. i-Swift enables logistics firms to improve their operations, promoting punctuality in deliveries and cutting operational expenses. Furthermore, educators and researchers in logistics, mathematics, and technology can benefit from i-Swift, offering applications for academic exploration.